Effect of Maternal Probiotic and Piglet Dietary Tryptophan Level on Performance and Piglet Intestinal Health Parameters Pre-Weaning - Dillon P. Kiernan; John V. O’Doherty; Marion T. Ryan; Torres Sweeney (Microorganisms, 2025)
A 2 × 3 factorial design was used to examine the effects of maternal probiotic supplementation (Bacillus subtilis and Bacillus amyloliquefaciens) and/or piglet dietary Trp levels on sow performance and fecal microbiota composition, as well as offspring pre-weaning performance and intestinal health parameters on the day of weaning. On day 83 of gestation, 48 sows were allocated to either: (1) control, or (2) control + probiotic (1.1 × 109 colony forming units/kg of feed). Their litters were assigned to 0.22, 0.27, or 0.33% standardized ileal digestible (SID) Trp diets (0.17, 0.21 and 0.25 SID ratio of Trp to lysine (Trp:Lys), SID lysine = 1.3%). At weaning, one piglet per litter was sacrificed for intestinal health analysis. Diet had no effect on sow reproductive or offspring growth performance pre-weaning (p > 0.05). Maternal probiotic supplementation led to distinct microbial communities in the sow feces on day 114 of gestation, increasing the relative abundance of Anaerocella and Sporobacter, while decreasing Lactobacillus, Ruminococcus, and Christensenella (p < 0.05). In the offspring colonic digesta, maternal probiotic supplementation increased Dorea, Sporobacter, and Anaerobacterium, while reducing the potentially harmful phylum Proteobacteria, specifically the family Enterobacteriaceae (p < 0.05), with a tendency for a reduction in the genus Escherichia (p < 0.1). Maternal probiotic supplementation enhanced duodenal morphology and modulated the expression of genes in the ileum, including a downregulation of certain immune and barrier defense genes (p < 0.05). Piglets from probiotic sows had reduced branch chain fatty acids (BCFA) in the cecal digesta and an increase in the total VFA and acetate in the colonic digesta (p < 0.05). There were limited effects of Trp level in the offspring’s creep diet or maternal × creep interactions, though this analysis was likely confounded by the low creep feed intake (total of ~0.83 kg/litter).